The Effect of Fertigation with Nano NPK Fertilizers on Some Parameters of Growth and yield of potato (Solanum tuberosum L.) - Hayyawi W.A.Al- juthery; Qusay M.N.Al-Shami (Al-Qadisiyah Journal For Agriculture Sciences, 2019)
A field experimentt has been carried out in the Autumn season of 2017 in one of the fields of the College of Agriculture - University of Qadisiyah to determine the response of the potato (Solanum tuberosum L.) to the fertigation with nano fertilizers of macro elements NPK on the growth and yield of the potato cultivar Arizona under drip irrigation system. The experiment has included 9 treatments of fertigation single Nano N, P, K, di combination nano (N+P), (N+K), (P+K), tri nano (N+P+K) and conventional fertilizers (NPK20:20:20) In addition to the comparative treatment, according to design of RCBD and one way simple treatment with 4 replicates . Fertilizers have been injected with levels of addition of 40L h-1of nano nitrogen fertilizer 25%N, 10 kg h-1 of nano phosphorus fertilizer 25% P and 20 kg h-1 of nano potassium fertilizer 35% K and 300 kg h-1 traditional fertilizer Tron (NPK 20:20:20) ) in four batches 10%, 20%, 30% and 40% of the quantities of fertilizers added to the first, second, third and fourth batches respectively. The growth parameters tested are plant height, chlorophyll content in leaves, vegetative dry matter yield, soft tubers yield, biological yield, dry tubers yield, starch, protein , The results of the Duncan test under a significant level of 0.05 showe that the following fertigation of nano (N+P+K) give has given the highest rate of vegetative qualities and the quality of all yield and significantly exceeded the di combinations and individual fertigation in some traits (plant height and chlorophyll content SPAD.higher nano(N+P+K) combination in the vegetative yield, the soft tubers yield, the biological yield, dry matter yield of tubers, the total yield protein and starch (2.148, 48.221, 11.395, 9.246,843. 871 and 6.355 Mg h-1 ) .